The diversity within an expanded and redefined repertoire of phase-variable genes in Helicobacter pylori. - Salaün, L; Linz, B; Suerbaum, S; Saunders, N (2004)
Phase variation is a common mechanism used by pathogenic bacteria to generate intra-strain diversity that is important in niche adaptation and is strongly associated with virulence determinants. Previous analyses of the complete sequences of the Helicobacter pylori strains 26695 and J99 have identified 36 putative phase-variable genes among the two genomes through their association with homopolymeric tracts and dinucleotide repeats. Here a comparative analysis of the two genomes is reported and an updated and expanded list of 46 candidate phase-variable genes in H. pylori is described. These have been systematically investigated by PCR and sequencing for the presence of the genes, and the presence and variability in length of the repeats in strains 26695 and J99 and in a collection of unrelated H. pylori strains representative of the main global subdivisions recently suggested. This provides supportive evidence for the phase variability of 30 of the 46 candidates. Other differences in this subset of genes were observed (i) in the repeats, which can be present or absent among the strains, or stabilized in different strains and (ii) in the gene-complements of the strains. Differences between genes were not consistently correlated with the geographic population distribution of the strains. This study extends and provides new evidence for variation of this type in H. pylori, and of the high degree of diversity of the repertoire of genes which display phase-variable switching within individual strains.